Controls of magma emplacement and 3d modelling of cupriferous basic bodies of the Kuperberg suite at Narrap mine, Okiep copper district, Namaqualand - Bester, Andeon (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.